Burden of cancer in a large consortium of prospective cohorts in Europe - Tsilidis, K; Papadimitriou, N; Capothanassi, D; Bamia, C; Benetou, V; Jenab, M; Freisling, H; Kee, F; Nelen, A; O'Doherty, M; Scott, A; Soerjomataram, I; et al. (Oxford University Press, 2016)
Disability-adjusted life-years (DALYs) are an indicator of mortality, morbidity, and disability. We calculated DALYs for cancer in middle-aged and older adults participating in the Consortium on Health and Ageing Network of Cohorts in Europe and the United States (CHANCES) consortium.A total of 90 199 participants from five European cohorts with 10 455 incident cancers and 4399 deaths were included in this study. DALYs were calculated as the sum of the years of life lost because of premature mortality (YLLs) and the years lost because of disability (YLDs). Population-attributable fractions (PAFs) were also estimated for five cancer risk factors, ie, smoking, adiposity, physical inactivity, alcohol intake, and type II diabetes.After a median follow-up of 12 years, the total number of DALYs lost from cancer was 34 474 (382 per 1000 individuals) with a similar distribution by sex. Lung cancer was responsible for the largest number of lost DALYs (22.9%), followed by colorectal (15.3%), prostate (10.2%), and breast cancer (8.7%). Mortality (81.6% of DALYs) predominated over disability. Ever cigarette smoking was the risk factor responsible for the greatest total cancer burden (24.0%, 95% confidence interval [CI] = 22.2% to 26.0%), followed by physical inactivity (4.9%, 95% CI = 0.8% to 8.1%) and adiposity (1.8%, 95% CI = 0.2% to 2.8%).DALYs lost from cancer were substantial in this large European sample of middle-aged and older adults. Even if the burden of disease because of cancer is predominantly caused by mortality, some cancers have sizeable consequences for disability. Smoking remained the predominant risk factor for total cancer burden.